Artífices da alteridade: o movimento indígena na região de Crateús - Ceará - Palitot, Estêvão Martins (2010)
My thesis analyses the construction of the indigenous movement in Ceará backlands, in the surrounding region of Crateús city. In this research, I focus on the understandings the processes of indigenous ethnic identity constructions (Tabajara, Potyguara, Kariri, Kalabaça, and Tupinambá peoples), within a context marked by social and political changes regarding citizenship and the role of cultural difference in contemporary political struggles. The proposed approach takes the indigenous movement as a process of specific social organization within a broader dynamic of translocal social and political articulation. Initially driven by catholic missionary action, in recent years, the indigenous movement has taken the public policies for indigenous people as its most significant counterpoint of dialogue and confrontation. Thus, the concepts of ethnogenesis and ethnification gain a centrality, within a line of reflection that includes ethnic groups as organizational and historically situated forms, allowing to analyze the process through which vectors of class, status and culture, typical of a complex society, are fixed in ethnic-based political units.